'Nasal flossing': A case report of nasopharyngeal stenosis due to severe erosive lichen planus and a novel therapeutic intervention. (2019) - Henry, Alastair; Biddlestone, John; McCaul, James
Highlights: An unusual case of nasopharyngeal stenosis following severe erosive oral lichen planus is described. Initial surgical management was complicated by recurrent nasopharyngeal stenosis due to the intense underlying inflammatory disease process. 'Nasal flossing' is described as a novel technique that can be used as an adjunct to prevent recurrence of nasopharyngeal stenosis and has relevance to a broad range of oral and nose and throat physicians. Abstract: Introduction: We describe a case of severe erosive oral lichen planus that led to nasopharyngeal stenosis. This is a rare clinical presentation that was ultimately, successfully treated by surgery combined with post-operative 'nasal flossing': a novel therapeutic intervention. Presentation of case: A 76-year-old male suffering from a rare case of severe oral lichen planus that was resistant to conservative measures is described. Initial surgery was complicated by recurrence of nasopharyngeal stenosis. Definitive surgery required revision of nasopharyngeal stenosis release combined with a course of post- operative 'nasal flossing'. The technique for 'nasal flossing' is described and demonstrated in photographs. The patient remained asymptomatic at 3 years using this combined approach, with restoration of olfaction, taste perception and voice quality, significantly enhancing quality of life. Discussion: Erosive oral lichen planus is a rare but important presentation in oral medicine. We found 'nasal flossing' to be a successful treatment to maintain nasopharyngeal patency following surgical repair of this uncommon condition. We are not aware that this combined approach has previously been described in the published literature. Conclusions: Severe erosive oral lichen planus can lead to nasopharyngeal stenosis. Nasopharyngeal stenosis in these patients may be refractive to conventional surgical approaches. 'Nasal flossing' is demonstrated to be both practical and acceptable as a surgical adjunct in these difficult to treat cases of recurrent nasopharyngeal stenosis. This report has relevance for all those practicing oral and maxillofacial surgery, ear nose and throat surgery and oral medicine.